IPO, as a new way to raise investments in Russian sports organizations - A. D. Askarov; U. A. Sukhanovskiy (Путеводитель предпринимателя, 2020)
In the article the analysis of now a days sposts economics situation in Russia and the mechanism of IPO, and plusses and minuses of it for Russian sports organizations.